2014
DOI: 10.1002/pbc.25071
|View full text |Cite
|
Sign up to set email alerts
|

Experience of barriers and motivations for physical activities and exercise during treatment of pediatric patients with cancer

Abstract: Interventions that aim at maintaining physical activities during treatment and eliminating exercise barriers are required due to the patients' positive attitudes and multiple motivations toward exercise. These interventions need to be supervised and should include health-counseling programs for patients, parents, and physicians to underline the importance of physical activities in childhood cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 42 publications
1
63
0
4
Order By: Relevance
“…Implementing strength exercises during acute treatment for pediatric cancer has already been shown as feasible [8,34] and desired by the patients [15]. Training, however, should always be done in a playful manner, should respect the interests and wishes of the child, and should follow general guidelines for strength training during childhood [12,27].…”
Section: Discussionmentioning
confidence: 99%
“…Implementing strength exercises during acute treatment for pediatric cancer has already been shown as feasible [8,34] and desired by the patients [15]. Training, however, should always be done in a playful manner, should respect the interests and wishes of the child, and should follow general guidelines for strength training during childhood [12,27].…”
Section: Discussionmentioning
confidence: 99%
“…Many pediatric oncology patients have reported that doctors do not engage in educating pediatric oncology patients and families about exercise (19, 32). Unfortunately, this is a recurring theme nationwide, even in patients who are healthy or who have other chronic illnesses (33, 34).…”
Section: Resultsmentioning
confidence: 99%
“…Götte et al reported that pediatric oncology patients and their families value their doctors’ opinions (32). Several physician intervention programs in healthy children have been shown to be successful in increasing PA in patients (14, 37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivations to exercise included desire to maintain or increase strength and CRF, fear of losing self-reliance due to weakness, feelings of normalcy, and positive side effects of exercise on mood, sleep, and quality of life. 67 Arroyave et al examined perceived barriers to improving exercise behaviors among AYA childhood cancer survivors, finding that the main barriers were fatigue, lack of time, and not belonging to a gym. 68 In a study of adolescent survivors of childhood cancer, Chung et al found that fatigue, decreased strength and endurance following treatment, and concern about academic performance prevented survivors from participating in regular physical activity.…”
Section: Barriers To Exercise and Intervention Preferences Of Childhomentioning
confidence: 99%